Local Culture-Based Education as an Alternative Pedagogical Model in Indigenous Regions - Maturbongs, Lodovika; Lestari, Slamet (Journal of Innovation and Research in Primary Education, 2025)
The preservation of local culture through education has become increasingly important in the context of globalization, particularly in culturally rich and peripheral regions such as Papua. This study aims to examine the implementation of local culture-based school programs in public senior high schools across Merauke Regency, focusing on forms of implementation as well as supporting and inhibiting factors. A qualitative approach with a multiple case study design was employed. Data were collected through semi-structured interviews, observations, and document analysis involving principals, teachers, extracurricular supervisors, and students from three public senior high schools. Data validity was ensured through source and method triangulation, and analysis followed the interactive model of data condensation, data display, and conclusion drawing. The findings reveal that local culture-based school programs are implemented through diverse models, including performance-based activities, curriculum-integrated projects, and holistic school culture approaches. Supporting factors include strong leadership commitment, culturally competent teachers, positive school culture, and community involvement, while inhibiting factors involve external cultural influences, limited resources, time constraints, and variations in teachers’ understanding. Notably, students demonstrated a strong preference for experiential and outdoor learning contexts when engaging with local culture. This study contributes to the discourse on culturally responsive education by providing empirical evidence from an indigenous context and highlights the importance of institutional integration and contextualized pedagogy in sustaining local culture-based education.